ANALYSIS OF MARKETING STRATEGIES AT POLITEKNIK LP3I JAKARTA, BEKASI CAMPUS (POLITEKNIK LP3I JAKARTA, 2026)
Increasing competition among higher education institutions requires universities to implement effective marketing strategies to attract prospective students. This study aims to identify and analyze the marketing strategies implemented by polytechnic LP3I Jakarta Bekasi Campus in increasing student enrollment. The research used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation related to campus marketing activities. The results show that the institution applies various marketing strategies, including social media promotion, school visits, seminars, and scholarship programs. In addition, the campus's advantage in preparing job-ready graduates has become one of its main attractions for prospective students. These strategies have been relatively effective in increasing student interest and enrollment. However, improvements in digital marketing are still needed to expand promotional reach and strengthen competitiveness among higher education institutions.